2022
DOI: 10.1080/21655979.2022.2065946
|View full text |Cite
|
Sign up to set email alerts
|

The biological function of the long non-coding RNA endogenous born avirus-like nucleoprotein in lung adenocarcinoma is mediated through the microRNA-655-3p/B-cell lymphoma-2 axis

Abstract: Lung adenocarcinoma (LUAD) is a subtype of lung cancer, and therapy remains a great challenge. A growing body of evidence shows that long-chain non-coding RNAs (lncRNAs) play an important role in the occurrence and development of LUAD. This study investigated the roles and mechanisms of action of EBLN3P in LUAD. The bioinformatics software starBase and TargetScan were used to predict the binding sites of the lncRNA endogenous born avirus-like nucleoprotein (EBLN3P) and microRNA (miR)-655-3p in LUAD. The regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Recent studies have demonstrated that lncRNAs are crucial regulators of tumor growth and invasion; they have reported that LNC EBLN3P can function as an oncogene in osteosarcoma and lung adenocarcinoma, and the inhibition of EBLN3P can be used in the treatment of cancer [14,15]. LNC EBLN3P can also promote the recovery of impaired spiral ganglion neurons by regulating the miR-204-5p/TMPRSS3 axis [16].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that lncRNAs are crucial regulators of tumor growth and invasion; they have reported that LNC EBLN3P can function as an oncogene in osteosarcoma and lung adenocarcinoma, and the inhibition of EBLN3P can be used in the treatment of cancer [14,15]. LNC EBLN3P can also promote the recovery of impaired spiral ganglion neurons by regulating the miR-204-5p/TMPRSS3 axis [16].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the expression of the NORAD was notably increased in cancer tissues and cells compared with that in normal tissues and cells in NSCLC, which regulates the proliferation, migration, and invasion capabilities of NSCLC cells by targeting the miR-520a-3p/PI3k/Akt/mTOR signaling pathways ( Wan et al, 2020 ). Wang et al revealed that the lncRNA, EBLN3P, was upregulated in lung adenocarcinoma cell lines (A549 and NCI-H23), inhibiting A549 cell viability and promoting apoptosis via the miR-655-3p/Bcl-2 axis ( Wang and Yin, 2022 ). CircRNA is a covalently closed loop-like structure that is highly specific to the eukaryotic transcriptome and can be used as a microRNA sponge, a splicer, and for transcribed gene expression ( Qu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EBLN3P can modulate the proliferation of lung adenocarcinoma cells through the miR-655-3p/Bcl2 axis. 36 Knockdown of EBLN3P hinders the proliferation, invasion, and migration of Jurkat cells by increasing miR-655-3p expression. 37 As for HuR, there is evidence that HuR-RNA interactions play essential roles in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%